Enhancing English Proficiency Skills Through Workshop - et. al., Hendar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study applied descriptive methods to determine the extent improvement of English Proficiency Test (EPT) score which was equivalent with TOEFL. The preparation workshop included skills and strategies workshop regarding to the TOEFL experience. This research purposed to describe the improvement as the result of workshop. The data collection techniques were (1) observation, (2) training, and (3) document analysis. The participants were assisted to discover of how to deal with TOEFL test type of questions. The sample is the training participants from 209 students came from several different major. The results of the data analysis showed that broadly speaking, there was a significant correlation between the preparation workshops and score achievement of EPT. The results indicated that the hardest part or section experienced by the students was structure and written expression 41%, while in the part of listening was 33%, meanwhile the easiest part assumed by the student was reading comprehension 26%. Based on the result, it was proved by the EPT score achieved by the students. The average score was 443, and the best score reached by the student was in the section of reading comprehension. It was in line with the result of the workshop described the ability of mastering the skills in TOEFL section